The Position of Adopted Children (Mangain) in Obtaining the Status of the Heirther According to the Batak Toba Traditional Instruction Law - Ning Adiasih (Green Publisher Indonesia, 2022)
The adoption of adopted children in the Toba Batak community is carried out in an open and cash way. The main reason in the Toba Batak community is the absence of descendants. The indigenous Batak Toba community itself adheres to a patrilineal system that is based on male/father lineage. The requirements for adopting children by the Toba Batak indigenous people are carried out according to the customs of the indigenous people, by carrying out a traditional ceremony